AIRCRAFT DETECTION AT LOW AND EXTREME LOW ALTITUDES THROUGH PASSIVE MACROWAVE RADIOLOCATION - R. G. Khekhnev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
This article deals with describing of the means of electrically charged aircraft detection while they are flying at low and extremely low altitudes (20-60 metres). The equation to count the range of detection that depends on parameters of static electrification of low altitude flying aircraft, on relief nature with its objects in the flying track, on the level of natural interferences on the range of infrared frequencies, on sensitivity of the device that registers the phenomena stated by the author is given.